Epidemiological Profile of Naive HIV-1/AIDS Patients in Istanbul: The Largest Case Series from Turkey - Yemisen, Mucahit; Aydin, Ozlem Altuntas; Gunduz, Alper; Ozgunes, Nail; Mete, Bilgul; Ceylan, Bahadir; Karaosmanoglu, Hayat Kumbasar; Yildiz, Dilek; Sargin, Fatma; Ozaras, Resat; TABAK, Ömer Fehmi (My University, 2014)
The aim of the study was to report the epidemiological profile of HIV-1 positive patients from, Istanbul, Turkey, which has one of the lowest HIV-1/AIDS prevalences in Europe. The patients were followed by ACTHIV-IST group which was established by the Infectious Diseases Departments of five teaching hospitals (three university hospitals and two public hospitals) in Istanbul, Turkey. The HIV-1positive patients were added to the standard patient files in all of the centers; these files were then transferred to the ACTHIV-IST database in the Internet. A total of 829 naiv-untreated HIV-1 positive patients were chosen from the database. The number of male patients was 700 (84.4%) and the mean age of the patients was 37 years (range, 17-79). In our study group 348 (42%) of the patients were married and 318 (38.7%) of the patients were single. The probable route of transmission was heterosexual intercourse in 437 (52.7%) patients and homosexual intercourse in 256 (30.9%) patients. In 519 (62.6%) patients the diagnose was made due to a screening test and in 241 (29.1%) patients, the diagnose was made due to an HIV-related/non-related disease. The mean CD4+ T cell number in 788 of the patients was 357.8/mm(3) (+/- 271.1), and the median viral load in 698 of the patients was 100,000 copies/mL (20-9,790,000). In Turkey, the number of HIV-1 positive patients is still low and to diagnose with a screening test is the most common way of diagnostic route.